Effect of Kinesiotaping on Quality of Life of Knee Osteoarthritis Patients - Aditya Paramitha; Rahmi Isma (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Knee osteoarthritis (OA) causes pain which limits functional activity and quality of life. Quadriceps femoris muscle strengthening with weight-pulley system is effective in improving functional activity. Kinesiotaping is known in reducing pain thus improving activity and quality of life. This study was to determine the effect of kinesiotaping in addition to weight-pulley system exercise on quality oflife in grade II and III knee OA patients. Methods: Participants were randomly assigned to intervention group (n=13) and control group (n=14). All participants were treated with weight-pulley system exercise for nine sessions meanwhile participants in intervention group received additional kinesiotaping. Pre- and post-intervention quality of life were evaluated using Medical Outcome Study Short Form-36 (SF-36). Results: There were differences in total score of SF-36, bodily pain, general health, vitality, and role emotional between intervention and control group; (90.53±8.23, 76.98±11.88; p=0.002), (83.75±16.86,67.31±17.3; p=0.022), (88.57±10.27, 72.69±12.18; p=<0.001), (93.93±7.64, 80.77±10.18; p=0.002) and (92.86±14.18, 74.37±24.17; p=0.027), respectively. Conclusion: Application of kinesiotaping in addition to weight-pulley system exercise improved quality of, particularly in bodily pain, general health, vitality and role emotional in grade II and III knee OApatients.